2019
DOI: 10.1038/s41598-019-51928-w
|View full text |Cite
|
Sign up to set email alerts
|

Neural oscillations during cognitive processes in an App knock-in mouse model of Alzheimer’s disease pathology

Abstract: Multiple animal models have been created to gain insight into Alzheimer’s disease (AD) pathology. Among the most commonly used models are transgenic mice overexpressing human amyloid precursor protein (APP) with mutations linked to familial AD, resulting in the formation of amyloid β plaques, one of the pathological hallmarks observed in AD patients. However, recent evidence suggests that the overexpression of APP by itself can confound some of the reported observations. Therefore, we investigated in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
4
4
0
1
Order By: Relevance
“…In the touchscreen PAL [ 41 ], male WT animals completed the maximum number of all 36 trials per session, accompanied by decreasing session duration. The increase in the percentage of correct trials is in accordance with observations in a similar study [ 42 ]. In the IntelliCage setup [ 43 , 44 ], learning curves indicated a constant learning effect in the female WT animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the touchscreen PAL [ 41 ], male WT animals completed the maximum number of all 36 trials per session, accompanied by decreasing session duration. The increase in the percentage of correct trials is in accordance with observations in a similar study [ 42 ]. In the IntelliCage setup [ 43 , 44 ], learning curves indicated a constant learning effect in the female WT animals.…”
Section: Discussionsupporting
confidence: 92%
“…One year later, Jacob et al observed neither consequences on cognitive performance in a touchscreen task nor age-dependent changes in a phase-amplitude coupling analysis, which was used as a measure of neurophysiological functioning, in 4.5 month old App NL-G-F mice. In accordance with our findings in the App NL-G-F model, these mice displayed a higher variability than WT control mice [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…The amounts of cerebral Aβ peptides, i.e., the humanized and modified Aβ42 from the App NL–G–F KI mice, were determined in this study using ELISA (KHB3441, Invitrogen, ThermoFisher). The Aβ extraction protocol reported here is similar to that in other studies using App NL–G–F KI mice ( Jacob et al, 2019 ; Rice et al, 2020 ). Initially, brain tissue sections of about 100 mg were thawed on ice in 1 mL of pre-cooled extraction buffer, which consisted of 5 M guanidine hydrochloride (GuHCl), 50 mM TRIS, and 1x protease inhibitor cocktail (Sigma-Aldrich), adjusted to pH = 8.…”
Section: Methodsmentioning
confidence: 66%
“…Behaviours that carry negative emotional valence are likely to generate strong memories that only partially reflect the full spectrum of memory function, and therefore arguably do not represent an accurate depiction of memory decline in APP NL-G-F mice 92 . Moreover, the use of inappropriate controls can be found in several studies assessing spatial memory, such as comparisons with other knock-in models (APP NL-F and APP NL ) and non-littermate wild-type mice 89,90,93,94 . Behavioural correlates of memory loss are necessary for determining the extent of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%